PECULIARITIES OF GLYCOME OF THE EYEBALL ON THE BACKGROUND OF MERCAZOLILE-INDUCED HYPOTHYROIDOSIS BY LECTINOGISTOCHEMISTRY DATA - Щур, М.Б.; Струс, Х.І.; Ященко, А.М.; Луцик, О.Д. (World of Medicine and Biology, 2016)
The lectin panel included PNA, HPA, SNA, LABA, WGA and CNFA, conjugated to horseradish peroxidase. Lectin receptor sites were visualized with 3,3’-diaminobenzidine in the presence of H2O2. For routine histological examination sections were stained haematoxylin and eosin. These modifications in rods and cones lectin labeling were supplemented with the increased CNFA binding in the areas of synaptic contacts in the outer and inner reticular layers, as well as with enhanced exposure of LABA receptor sites (αLFuc) in pericarions of amacrine and ganglionic neurons of retina. In the cornea under experimental hypothyroidism it was detected reduction of HPA and CNFA labeling (αDGalNАc and GalNAc(β1-4)GlcNAc determinants) in the anterior epithelium, which was accompanied with the increased reactivity of these same lectins with stromal keratocytes and collagen fibers. Reported drift in corneal lectin binding apparently indicates negative influence of hypothyroidism on epithelial adhesion to Bowman’s membrane and corneal transparency conditions, the latters depending on crystallins and keratan sulphates produced by keratocytes. Detected rearrangements in carbohydrate determinants of retinal compartments presumably reflect alterations in the functional activity of neurons and subsequent disturbancies in nerve impulses transduction. Lectins WGA, CNFA, LABA and HPA can be recommended for selective histochemical labeling of structural components of the rat eyeball.